The program me of Pyatigorsk state university on counter extremism activities on the territory of the educational organization and student dormitories - D. Kondrakova, Elvira (International Journal of Engineering and Technology, 2018)
The relevance of the research is conditioned by the necessity to arrange countermeasures against extremism on the territory of the educational organization and student dormitories, and by the absence of a scientifically justified model for operation of universities in this direction. Research goal: theoretical justification and elaboration of the programme on counter-extremism activities on the territory of the educational organization and student dormitories. The leading research methods were the analysis and generalization of the pedagogic experience, statistical processing of the quantitative data concerning the problem state in the educational organization, and simulation. The research results contribute to further scientific comprehension of the problem of preventing extremist manifestations among the youth in the present socio-cultural situation and to creation of the required conditions for successful fulfillment of the anti-terrorist and anti-extremist line of the government. The programme for extremism prevention in the student environment was presented, the introduction of which will allow achieving a positive effect in educating a personality that can express the Russian spiritual and moral imperative, has a proactive attitude with regard to opposing asocial phenomena, radicalism, extremism, and terrorism in all forms; the socio-cultural conditions for preventing the extremist attitudes that contribute to pedagogic correction in the process of educational and leisure activities were revealed. Research value: the research showed that applying a complex of preventive measures with due account for the organizational-pedagogic, socio-psychological, professional socio-cultural conditions largely optimizes the activity on introduction of conceptual provisions of the state youth policy, and reduces the level of destructive behaviour in the student environment. The materials of the paper can be useful for the heads of educational structures of different level and other subjects of educational activity, and can be used in the outreach and volunteer activities of the youth non-governmental organizations.Â Â